Temperature driven hibernation site use in the Western barbastelle Barbastella barbastellus (Schreber, 1774) - Luc De Bruyn (Nature Portfolio, 2021)
Abstract In temperate regions, winter is characterized by cold temperatures and low food availability. Heterothermic animals can bridge this period by entering a state of torpor characterized by decreased body temperature and reduced metabolic rate. Hibernation site choice is crucial since temperature conditions in the hibernaculum will impact torpor. We analysed temperature-dependent hibernation site use of Barbastella barbastellus. Bats and temperature were monitored in an underground system (1999–2019) and standalone bunkers (2007–2019) in Western Poland. During the winter of 2017–2018 we analysed the thermal variability of the hibernacula. Seasonal variation is higher in bunkers and thus temperatures get colder in winter than in the underground system. On the other hand, short-term variability (thermal variability index) in the bunkers was lower than in the underground system. This makes bunkers a more stable environment to hibernate for cold dwelling bats in warm winters, when temperatures in the bunkers do not get below freezing. Bats use both the warm underground system and the colder bunkers. During the last decade, a continuous series of warm winters occurred and the population of barbastelle bats partly moved from the underground system to the bunkers. These present temperature increases broadened the range of potential hibernation sites for barbastelles. Our study indicates that long-term trends, seasonal variation and short-term variability in temperatures are all important and should be analysed to investigate hibernaculum use by bats. Our study shows that small hibernation sites may become more important in the future.